An Analysis of the Bibliometric Network on the Impact of Digital Business on Tourism - Shakeel Basher (Journal of Social Responsibility, Tourism and Hospitality, 2023)
The purpose of this article is to map the state of E-tourism business tourism research and the connections between these subjects. Using VOSviewer, the bibliometric analysis method helps us visualize and analyze patterns such as co-occurrence of keywords, co-citations of cited authors, and co-citations of cited sources. It also helps us understand the structure related to the topic under study. The Scopus database's 98 publications on etourism- related subjects are examined in total. We discover that since 2008, the trend in etourism research has not substantially grown. Additionally, we identified study subjects that may be investigated using trending keywords. Furthermore, we identified the most influential writers and publications on the subject of e-business and tourist research, as well as the connections between them. To the best of our knowledge, this study is the first to use VOSviewer for bibliometric analysis on the subject of e-Tourism and tourism concurrently. 98 publications were thoroughly reviewed.